Geochronology and petrogenesis of Carboniferous and Triassic volcanic rocks in NW Laos: Implications for the tectonic evolution of the Loei Fold Belt. (1st April 2021) - Shi, Meifeng; Zaw Khin,; Liu, Shusheng; Xu, Baoci; Meffre, Sebastien; Cong, Feng; Nie, Fei; Peng, Zhimin; Wu, Zhenbo
Graphical abstract: Highlights: The Loei Fold Belt contains Late Carboniferous (304–299 Ma) basaltic and andesitic tuffaceous rocks and Late Triassic (224–236 Ma) andesite and rhyolite. The Late Carboniferous and Late Triassic volcanic rocks were formed in a back-arc basin and continental arc setting respectively. Magmatic events in the Loei Fold Belt occurred in four periods: Ordovician-Silurian, Late Devonian-Middle Permian, Early-Middle Triassic and Late Triassic. The Nan belt and Luang Prabang-Loei belt were connected in a back-arc basin during Late Devonian to Carboniferous. Abstract: The Loei Fold Belt is one of the most significant tectonic and metallogenic belts in the Indochina Block. However, origin and tectonic significance of volcanic rocks in several volcanic belts of this fold belt remain ambiguous. In this paper, we present new petrochemical data, zircon U-Pb ages and Lu-Hf isotopic data for volcanic rocks from the Loei Fold Belt in northwestern Laos. The basaltic and andesitic tuffaceous rocks have Late Carboniferous zircon U-Pb ages (304 ± 2.1 Ma and 299 ± 1.8 Ma respectively), and display both MORB-like and arc-like geochemical signatures. Zircon Lu-Hf isotopic analyses give highly positive εHf (t) values of 8.99–14.24, indicative of a metasomatic mantle source which formed in a back-arc basin environment. On the other hand, the andesite and rhyolite samples have zircon U-Pb ages ranging from 236 Ma to 224 Ma, erupted during the Late Triassic, and formed in a continental margin arc setting (e.g., enrichment of LREE, depletion in Nb-Ta, Sr, and positive εHf (t) values of 9.87–12.25). With a synthesis of available geochronological, petrochemical and isotopic data, magmatic events in the Loei Fold Belt occurred in four periods: Ordovician-Silurian (450–400 Ma), Late Devonian-Middle Permian (ca. 361–265 Ma), Early-Middle Triassic (250–237 Ma) and Late Triassic (ca. 236–200 Ma), with peaks in Triassic and Carboniferous. Accordingly, we propose a tectonic-magmatic evolution model for the Loei Fold Belt. The Luang Prabang-Loei belt was a spreading back-arc basin during the Late Devonian-Middle Permian, and connected with the Nan back-arc basin. The basin expanded to its largest extent in the Permian period and started subduction in the earliest Triassic; the successive subduction did not terminate until the Late Triassic.